Power training and the effect on pain in osteoarthritis - Nygård, Lisette (2019)
Aims. Power training as a suitable training method for older adults but power training is not yet included in exercise recommendations for persons with osteoarthritis. Since many patients with osteoarthritis suffer from pain, the purpose of this study was to investigate if power training can decrease pain in persons with knee or hip osteoarthritis.